2014
DOI: 10.17221/7585-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effects of laying hens housing system on laying performance, egg quality characteristics, and egg microbial contamination

Abstract: ABSTRACT:The objective of this study was to compare the performance, egg quality, and microbial contamination of egg shells from hens maintained in different housing systems, such as conventional and enriched cages, litter, and aviaries. The housing system significantly (P < 0.001) influenced the performance characteristics. The highest egg production, lowest daily feed consumption, and feed conversion ratio were measured in conventional cages compared to litter and aviaries. Higher egg shell and albumen quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
68
3
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(92 citation statements)
references
References 28 publications
13
68
3
8
Order By: Relevance
“…Eggs were heavier in enriched cages (P ≤ 0.043) compared to the litter system (Table 1). These results correspond with the findings of Englmaierova et al (2014) who detected heavier eggs in the cage system compared to litter. On the other hand, Tumova and Ebeid (2005) and Pistekova et al (2006) detected heavier eggs in litter systems compared to conventional cages.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Eggs were heavier in enriched cages (P ≤ 0.043) compared to the litter system (Table 1). These results correspond with the findings of Englmaierova et al (2014) who detected heavier eggs in the cage system compared to litter. On the other hand, Tumova and Ebeid (2005) and Pistekova et al (2006) detected heavier eggs in litter systems compared to conventional cages.…”
Section: Resultssupporting
confidence: 92%
“…Similarly, Ledvinka et al (2012) and Englmaierova et al (2014) found stronger shells in cages than in litter system. Studies on the effect of housing system on cuticle deposition are very limited and need more investigations.…”
mentioning
confidence: 76%
“…Six eggs from each light colour (2 eggs from upper floor, 2 eggs from middle floor and, 2 eggs from lower floor) in one collection were analyzed, in total 120 eggs. Microbial analysis of the eggshell surface was performed on fresh eggs according to Englmaierova et al (2014). The eggs were sampled by hand (wearing clean gloves), placed on a clean underlay.…”
Section: Methodsmentioning
confidence: 99%
“…The average of 1.5% reduced egg production on organic farms in Leenstra et al (2012) was the average of non-significant differences between the systems in Switzerland and France, and a significant 5.7% lower egg production on organic farms in the Netherlands. Three of the studies (Dekker et al, 2011a;Englmaierová et al, 2014;Leenstra et al, 2014) showed that feed conversion ratio was 5.5 to 28.1% higher in organic compared to conventional production ( Figure 3.7). The higher feed conversion ratio of organic laying hens, as compared to laying hens kept in conventional cage housing, is partly inherent to the loose hen housing in the organic system, in which laying hens have a higher energy expenditure due to higher activity levels and outdoor access.…”
Section: Laying Hensmentioning
confidence: 98%
“…Dekker et al (2011a) used normative data for the conventional system, whereas data for the organic system were obtained from interviews with 20 randomly selected organic farmers. Englmaierová et al (2014) compared 72 conventional laying hen farms with 72 organic farms. Leenstra et al (2012) collected data on 257 farms in three countries (Switzerland, France and the Netherlands).…”
Section: Laying Hensmentioning
confidence: 99%